1994
DOI: 10.1177/089686089401400405
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic Mesh Repair of Multiple Recurrent and Large Abdominal Hernias in Continuous Ambulatory Peritoneal Dialysis Patients

Abstract: Objective The aim of this study was to find out whether prosthetic mesh repair of recurrent and large abdominal hernias in continuous ambulatory peritoneal dialysis (CAPD) patients is effective in maintaining them on CAPD. Design Retrospective analysis of case notes over a period of 5 years. Setting Single renal unit of a university hospital. Patients Forty-six of 217 CAPD patients (16%) had their hernias repaired. Among them, 5 women in whom hemodialysis was not possible had multiple or large hernias repaired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
16
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 17 publications
3
16
1
Order By: Relevance
“…Although CAPD was re-instituted as soon as 1 to 3 days after surgery, none of our patients experienced early or late leakage or a hernia recurrence, irrespective of the localisation of the hernia. This is in accordance with excellent results reported in the literature (9). Failure of this surgical technique for hernia repair is rare although it has been reported in the literature (10).…”
Section: Discussionsupporting
confidence: 90%
“…Although CAPD was re-instituted as soon as 1 to 3 days after surgery, none of our patients experienced early or late leakage or a hernia recurrence, irrespective of the localisation of the hernia. This is in accordance with excellent results reported in the literature (9). Failure of this surgical technique for hernia repair is rare although it has been reported in the literature (10).…”
Section: Discussionsupporting
confidence: 90%
“…A large volume of dialysate is prescribed to improve the peritoneal small molecule clearance in order to make the clinical target level adequate [1]. Hernia has been found to be more prevalent among peritoneal dialysis patients than in the general population, with its reported frequencies of 10% to 25% and with an incidence of 0.06 hernias per dialysis year [3,[6][7][8]. A few studies have reported that pre-existing hernias were detected in 5.5% to 12.3% of peritoneal dialysis patients before CAPD was initiated on the patient [1,3,9].…”
Section: Discussionmentioning
confidence: 99%
“…The traditional operation method for abdominal wall hernia repair in peritoneal dialysis patients requires discontinuing the peritoneal dialysis for a long period of days to weeks after the operation to prevent damage of the repair site [12]. Polypropylene mesh repair was recently used for hernias of patients on CAPD [3,7,13]. Low-tension mesh repair provides a technically simple solution to the many surgical disadvantages of CAPD patients [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abdominal hernias are not as common as they were 15–20 years ago when peritoneal dialysis (PD) catheters were placed in the midline (1). These and inguinal hernias, however, are still seen in 2%–15% of PD patients (2–5).…”
mentioning
confidence: 99%